(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2023)
Environmental sanitation is an important concept in Islam which teaches to maintain cleanliness and health, because cleanliness is part of faith. Sanitation also refers to maintaining hygienic conditions through efforts to provide facilities and services for the disposal of human waste such as urine and feces. Poor sanitation conditions will have a negative impact on many aspects of life, starting from the decline in the quality of the community’s living environment, contamination of drinking water sources for the community, increasing the number of diarrhea cases and the emergence of several diseases. In the Lumpatan Community Health Center working area, there are still many residents who do not have their own toilets at home and still carry out defecation activities in the river using bong toilets. This research is quantitative research, using a cross sectional method. This research was conducted from 8 to 13 June 2022 at the Lumpatan Community Health Center, Musi Banyuasin Regency. The population in this study was 11,141 families. Next, to determine the sample per village using purposive sampling. The results of the research found that 71 respondents (71.7%) did not have healthy toilets, 64 respondents (64.6%) had poor knowledge, 60 respondents (64.6%) had a supportive attitude, 55 respondents (60.6%) had low income. .6%), low education 61 respondents (61.6%), good role of health workers 59 respondents (59.6%), support from community figures who support 55 respondents (55.6%), and respondents who do not work 64 respondents (64.6%).